Análise Retrospectiva de Fatores de Risco e Preditores de Complicações Intraoperatórias dos Bloqueios do Neuroeixo Realizados na Faculdade de Medicina de Botucatu-UNESP - Pereira, Ivan Dias Fernandes [UNESP]; Grando, Marcela Miguel [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Vane, Luís Antônio [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Júnior, Paulo do Nascimento [UNESP]; Amorim, Rosa Beatriz [UNESP]; Júnior, Geraldo Rolim Rodrigues [UNESP]; Braz, Leandro Gobbo [UNESP]; Ganem, Eliana Marisa [UNESP] (Elsevier, 2011)
Background and objectives: Cardiovascular changes associated with neuraxial blocks are a cause of concern due to their frequency and because some of them can be considered physiological effects triggered by the sympathetic nervous system blockade. The objective of this study was to evaluate intraoperative cardiovascular complications and predictive factors associated with neuraxial blocks in patients ≥ 18 years of age undergoing non-obstetric procedures over an 18-year period in a tertiary university hospital - HCFMB-UNESP. Methods: A retrospective analysis of the following complications was undertaken: hypertension, hypotension, sinus bradycardia, and sinus tachycardia. These complications were correlated with anesthetic technique, physical status (ASA), age, gender, and preoperative co-morbidities. The Tukey test for comparisons among proportions and logistic regression was used for statistical analysis. Results: 32,554 patients underwent neuraxial blocks. Intraoperative complications mentioned included hypotension (n = 4,109), sinus bradycardia (n = 1,107), sinus tachycardia (n = 601), and hypertension (n = 466). Hypotension was seen more often in patients undergoing continuous subarachnoid anesthesia (29.4%, OR = 2.39), ≥ 61 years of age, and female (OR = 1.27). Conclusions: Intraoperative hypotension and bradycardia were the complications observed more often. Hypotension was related to anesthetic technique (CSA), increased age, and female. Tachycardia and hypertension may not have been directly related to neuraxial blocks. © 2011 Elsevier Editora Ltda.
Retrospective analysis of risk factors and predictors of intraoperative complications in neuraxial blocks at faculdade de medicina de botucatu-UNESP
Keywords: Anesthesia, Epidural; Anesthesia, Spinal; Arrhythmias, Cardiac; Hypertension; Hypotension; Intraoperative Complications